The Defender's Dilemma Charting a Course Toward Cybersecurity - Libicki, Martin C. (RAND Corporation, 2015)
Cybersecurity is a constant, and, by all accounts growing, challenge. This report, the second in a multiphase study on the future of cybersecurity, reveals perspectives and perceptions from chief information security officers; examines the development of network defense measures-and the countermeasures that attackers create to subvert those measures; and explores the role of software vulnerabilities and inherent weaknesses.